Nutritional assessment of Tithonia diversifolia in the feeding of New Zealand white rabbits - Rizzo Zamora, Lauden Geobakg (2019)
The objetives were to determine the digestibility in vivo and the productive behavior in rabbits fed with foliage flour of Tithonia diversifolia in substitution of the balanced one. The treatments were: T0 = Balanced 100%; T1 = Balanced 75% + 25% Tithonia diversifolia flour; T2 = Balanced 50% + Tithonia diversifolia flour 50%; T3 = Balanced 25% + 75% Tithonia diversifolia flour and T4 = 100% Tithonia diversifolia flour. A complete randomized design (CRD) with four replications was applied. to assess digestible energy (DE). 20 male rabbits with an average weight of 1400 g were used and 40 weaned male rabbits with an average weight of 250 g were used for the productive performance. To establish the difference between means, the Tukey test (P<=0.05) was applied. Digestibility of dry matter (DM %), organic matter (OM%), crude protein (CP%), Raw fiber (RF%), Ethereal extract (EE%) nitrogen-free extract (NFE%), digestible energy (DE kcal/kg), total digestible nutrients (TDN%), ashes (A%), food consumption (FC g), Weight gain (WG g), Food conversion index (FCI) and yield to the carcass (YC)% was evaluated. The treatment T3 (69.60%) recorded the best DRF (P <0.05). The best WG and FCI were recorded by treatments T0, T1 and T2 (1,600.44 g and 3.75), (1,548.12 g and 3.87) and (1,438.12 g and 4.17), respectively.